An integrated smart framework for fast-moving consumer goods online market logistics: a digital twin framework - Ghanavatinejad, Mohssen; Tavakoli, Mahdieh; Sheikhalishahi, Mohammad; Aydin, Nezir; Aria, Seyed Sina (TAYLOR & FRANCIS LTD, 2025)
This study develops an integrated smart framework to enhance logistics performance in the fast-moving consumer goods (FMCG) sector. Utilizing advanced technologies such as Internet of Things (IoT), Radio Frequency Identification (RFID), and automation, the research addresses key challenges in FMCG logistics, including delivery delays and errors. A digital twin approach is utilized to model logistics processes, analyze various scenarios, and assess the efficacy of these technologies. The findings show that smart technologies significantly reduce delivery errors, improve delivery times, and boost customer satisfaction. Specifically, the smart logistics model achieved an efficiency rate of 96%, in contrast to 83% observed in the traditional model. Furthermore, the rate of incorrectly delivered products decreased dramatically from 4.3% in the traditional system to 0.4% in the smart system. The managerial implications of this study provide a comprehensive roadmap for the integration of smart logistics technologies, fostering a competitive advantage in the dynamic FMCG market.
Keywords: Smart logistics; digital twin; fast-moving consumer goods (FMCG); online market; SUPPLY CHAIN; SYSTEM; MANAGEMENT; OPTIMIZATION; SIMULATION; DELIVERY; INTERNET; DESIGN; Engineering